Analysis of the influence of workload, work motivation, and work environment on the performance of production employees in the manufacturing sector at Cv.Restu Ibu, Sukoharjo Regency - Ainun Nandini; Zandra Dwanita Widodo; Atik Lusia (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to analyze the influence of work load, work motivation, and work environment on the performance of production employees in the manufacturing sector at Cv.Restu Ibu in Sukoharjo Regency. This study uses a quantitative method with data collection techniques using questionnaires with characteristics (Purposive Sampling) of permanent production employees with at least one year of work experience by distributing questionnaires to 75 employees. The hypothesis testing used in this study is a descriptive analysis technique using SPSS version 27 for Windows software. The results of this study indicate that 1) Workload has a negative and significant effect on the performance of employees at CV. Restu Ibu Kabupaten Sukoharjo. 2) Work motivation has a positive effect but does not significantly affect the performance of employees at CV. Restu Ibu in Sukoharjo Regency. 3) Work environment has a positive and significant effect on the performance of employees at Cv. Restu Ibu in Sukoharjo Regency. 4) Workload, work motivation, and work environment together have a significant effect on the performance of employees at Cv. Restu Ibu in Sukoharjo Regency. The coefficient of determination (Adjusted R²) value of 0.231 shows that 23.1% of employee performance variables can be explained by workload, work motivation, and work environment. These findings indicate that the key to improving performance at Cv. Restu Ibu lies in good human resource management, a balanced workload, good work motivation through periodic evaluations, and a supportive work environment.